Cyclotron produced radionuclides: Physical characteristics and production methods - International Atomic Energy Agency (International Atomic Energy Agency, 2013)
Application of radioisotopes has shown significant growth in the past decade, and a major factor contributing towards this growth is the availability of a large number of cyclotrons dedicated to the production of radioisotopes for medical applications. Although there are many articles in journals on cyclotrons and their use for radioisotope production, there is no single source of information for beginners on radioisotope production using cyclotrons. This publication attempts to address this deficiency. It contains chapters on accelerator technology, theoretical considerations of nuclear reactions, the technology behind targetry, techniques on preparation of targets, irradiation of targets under high beam currents, target processing and target recovery